Integration of Intercultural Learning into an International Advanced Pharmacy Practice Experience in London, England - Ellen Schellhase; Ishmum Hasan; Stephanie Hendricks; Monica L. Miller (MDPI AG, 2021)
As the number of international advanced pharmacy practice experiences (APPEs) continues to grow, this is an opportunity to incorporate intercultural learning (ICL) to further advance student pharmacist training. Purdue University student pharmacists participated in a clinical research focused APPE in London, England. To prepare for this APPE, students completed a one-credit course focused on intercultural learning and travel preparation. The purpose of this report is to describe the implementation and assessment of ICL during this course and international APPE. The course includes interactive ICL activities, reflective assignments, and personalized assessments. During the eight-week APPE, student pharmacists worked on an individualized Intercultural Development Plan®, which includes ICL activities, focused reflection, and check-ins. ICL was assessed using the Intercultural Development Inventory® (IDI®) at the beginning of the course and at least four weeks after APPE completion. Student APPE feedback was also reviewed for evidence of ICL. Twenty-seven students completed the course and APPE from 2018 to 2020. The average IDI developmental orientation (DO) before the course was 91.7, placing students in minimization. The average perceived orientation was 120.9, placing students in acceptance. There were 18 students who completed the post-APPE IDI: 12 students demonstrated growth in the DO (range: 1.5-23.72), and six students experienced a decrease in their DO. Intercultural learning can be implemented and assessed as part of an international APPE.